Analisis dan Pengembangan Sistem Informasi Pengelolaan Masjid berbasis Mobile dengan Teknologi API Web Service - Mujahid, Ahmad; Abdullah, Muhammad Yahya; Suharya, Suharya; Adriansyah, Ahmad Rio (Jurnal Informatika Terpadu, 2021)
YukAmal (yukamal.com) is a web-based mosque information and management system. Feature on YukAmal website is a donation, finance, construction progress, and information mosques. At present, the application cannot integrate with mobile apps. The research aims to design the YukAmal application based on Android Kotlin, integrated using REST API web service technology. The method applied in this research uses Scrum to get optimal results. This application divide into three modules: Information and Mosque Search, Donation and Mosque Finance, and REST API Web Service. The method used is UAT (User Acceptance Testing). For web service, REST API feature gets 85% test results, mosque information features and online donations get 80% test results, financial report feature gets 25% test results or can only view financial information. Results of the research, this application was proper for use by worshipers and mosque administrators in Depok City.